Redox-switchable breathing behavior in tetrathiafulvalene-based metal–organic frameworks - Jian Su (Nature Portfolio, 2017)
Modulating the adsorption behaviours of metal-organic frameworks using external stimuli is desirable, but challenging to achieve. Here, Zhou and colleagues design an indium-based MOF in which tetrathiafulvalene ligands undergo reversible redox reactions that alter the framework breathing behaviour.